1953
DOI: 10.2527/jas1953.124775x
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between Meat Production Characters and Body Measurements in Beef and Milking Shorthorn Steers

Abstract: B ODY conformation in cattle is one of the important bases in judging and selecting animals for breeding and production purposes. Measurements taken on various parts of the body furnish an objective description of body conformation. The ability of cattle to produce meat could be estimated with these measurements if relationships between body measurements and meat production characters were obtained. A number of studies have been made on the relations of certain body measurements to some of the performance fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

1956
1956
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 3 publications
0
3
0
1
Order By: Relevance
“…Esta información podría ser utilizada en la predicción del rendimiento de carcasa y la edad de beneficio apropiado. Hammack y Shrode (1986) señalan que el peso y algunas medidas corporales como la longitud corporal y el ancho de caderas son útiles para predecir los pesos de carcasa en vacunos de carne; así mismo, Yao et al (1953) encontraron en bovinos de carne que el diámetro y circunferencia muscular estaban positivamente correlacionadas con el grado de la canal. En base a estas informaciones, se puede inferir que el área de la grupa y el volumen del muslo deben guardar estrecha relación con el rendimiento de la carcasa, ya que son zonas de gran desarrollo muscular, hecho que debe corroborarse en la llama.…”
Section: Discussionunclassified
“…Esta información podría ser utilizada en la predicción del rendimiento de carcasa y la edad de beneficio apropiado. Hammack y Shrode (1986) señalan que el peso y algunas medidas corporales como la longitud corporal y el ancho de caderas son útiles para predecir los pesos de carcasa en vacunos de carne; así mismo, Yao et al (1953) encontraron en bovinos de carne que el diámetro y circunferencia muscular estaban positivamente correlacionadas con el grado de la canal. En base a estas informaciones, se puede inferir que el área de la grupa y el volumen del muslo deben guardar estrecha relación con el rendimiento de la carcasa, ya que son zonas de gran desarrollo muscular, hecho que debe corroborarse en la llama.…”
Section: Discussionunclassified
“…Wanderstock and Salisbury (1946) reported similar high correlations between weight at slaughter and height at withers and heart girth. However, Yao et al (1953) reported low correlations between the variables related to the height at hooks, the width of the chest (r = -0.07) and the width at pelvis (r = 0.17). These earlier results were in agreement with the low correlations estimated in the present study.…”
Section: Table 1 Means Standard Deviations (Sd) and Coefficients Of Variation (Cv) Of The Measurements Of Different Breeds (Dairy N=169; mentioning
confidence: 91%
“…Severson and Gerlaugh (1917), Lush (1932), Hankins and Beard (1944), and Yao, Dawson, and Cook (1953) report that width, depth, and circumference measurements are mainly fleshing measurements. These measurements quite highly reflect the amount of finish which a particular steer or sheep possesses.…”
Section: Beef and Sheep Evaluation Techniquesmentioning
confidence: 99%